Association between preoperative C-reactive protein to albumin ratio and late arteriovenous fistula dysfunction in hemodialysis patients: a cohort study - Shouliang Hu; Runjing Wang; Tean Ma; Qingfeng Lei; Fanli Yuan; Yong Zhang; Dan Wang; Junzhang Cheng (Scientific Reports, 2023)
Abstract Arteriovenous fistula (AVF) dysfunction is a critical complication in hemodialysis (HD) patients, with inflammation potentially contributing to its development. This retrospective cohort study aimed to investigate the association between preoperative C-reactive protein to albumin ratio (CAR) and AVF dysfunction in Chinese HD patients. A total of 726 adults with end-stage renal disease who underwent new AVF placement between 2011 and 2019 were included. Multivariable Cox regression and Fine and Gray competing risk models were employed to assess the relationship between CAR and AVF dysfunction, considering death and renal transplantation as competing risks. Among 726 HD patients, 29.2% experienced AVF dysfunction during a median follow-up of 36 months. Adjusted analyses revealed that higher CAR levels were associated with an increased risk of AVF dysfunction, with a 27% higher risk per one-unit increase in CAR. Furthermore, patients with CAR values ≥ 0.153 exhibited a 75% elevated risk compared to those with CAR values < 0.035 (P = 0.004). The relationship between CAR and AVF dysfunction varied by the site of internal jugular vein catheter placement (P for trend = 0.011). Notably, the Fine and Gray analysis confirmed the association between CAR and AVF dysfunction, with a 31% increased risk per one-unit increase in CAR. The highest CAR tertile remained an independent predictor of AVF dysfunction (HR = 1.77, 95% CI 1.21–2.58, P = 0.003). These findings highlight the potential of CAR as a prognostic marker for AVF dysfunction in Chinese HD patients. Clinicians should consider CAR levels and catheter placement site when assessing the risk of AVF dysfunction in this population.